Nichtlineare Schwingungen von Systemen mit elastohydrodynamischen Linienkontakten - Wiegert, Benedikt (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2015)
The influence of elastohydrodynamic contacts (EHL) on the nonlinear vibration behaviour of mechanical systems is investigated. A continuously modelled EHL contact is computationally expensive. Therefore, a simplified contact model, which is particularly suitable for oscillatory systems with numerous contacts, has to be developed and validated. Based on basic models, nonlinear oscillation phenomena induced by EHL contacts are discussed. Moreover, a rotor in cylinder roller bearings is considered.